The American Western - McVeigh, Stephen (Edinburgh University Press, 2007)
This wide-ranging book illuminates the importance of the Western in American history. It explores the interconnections between the Western in both literature and film and the United States in the 20th century. Structured chronologically, the book traces the evolution of the Western as a uniquely American form. The author argues that America's frontier past was quickly transformed into a set of symbols and myths, an American meta-narrative that came to underpin much of the 'American century'. He details how and why this process occurred, the form and function of Western myths and symbols, the evolution of this mythology, and its subversions and reconstructions throughout 20th-century American history. The book engages with the full range of historical, literary and cinematic perspectives and texts, from the founding Western histories of Theodore Roosevelt and Frederick Jackson Turner to the New Western history of Patricia Nelson Limerick and Richard White. Key texts used to illustrate the narrative include: *Owen Wister's The Virginian*Jack Schaefer's Shane*Cormac McCarthy's Blood Meridian*Ishmael Reed's Yellow Back Radio Broke Down*Films from Edwin Porter's The Great Train Robbery to Fred Zinneman's High Noon and from Clint Eastwood's Unforgiven to the post 9/11 Westerns Open Range, The Alamo and Brokeback Mountain This book is an essential and comprehensive analysis of the significance and enduring legacy of the American Western. Key Features: *Includes chapters on Western history, literature and film*Shows the interconnections between the Western (in all its forms) and 20th-century American history, politics, culture and society*The only book to take a multi-disciplinary approach to the subject